The effects on stature of poverty, family size and birth order: British children in the 1930s - Timothy J. Hatton; Richard M. Martin (Institute for the Study of Labor (IZA), 2008)
This paper examines effects of socio-economic conditions on the standardised heights and body mass index of children in Interwar Britain. It uses the Boyd Orr cohort, a survey of predominantly poor families taken in 1937-9, which provides a unique opportunity to explore the determinants of child health in the era before the welfare state. We examine the trade-off between the quality (in the form of health outcomes) and the number of children in the family at a time when genuine poverty still existed in Britain. Our results provide strong support both for negative birth order effects and negative family size effects on the heights of children. No such effects are found for the body mass index (BMI). We find that household income per capita positively influences the heights of children but, even after accounting for this, the number of children in the family still has a negative effect on height. This latter effect is closely associated with overcrowding and particularly with the degree of cleanliness or hygiene in the household, which conditions exposure to factors predisposing to disease. We also analyse evidence collected retrospectively, which indicates that the effects of childhood conditions on height persisted into adulthood.
Keywords: J13; 360; Child health; heights; poverty; Kinder; Gesundheit; Armut; Haushaltseinkommen; Familie; Großbritannien